2019
DOI: 10.12659/msm.912947
|View full text |Cite
|
Sign up to set email alerts
|

Foot Morphology in Chinese Adolescents Aged Between 13 to 18 Years Varies by Gender and Age

Abstract: BackgroundWe recently reported age and gender differences in foot shape and size in Chinese school children aged between 7–12 years. This study aimed to analyze age and gender differences in foot shape and size in Chinese adolescents aged between 13–18 years.Material/MethodsThe study included 1,252 adolescent boys and 1274 adolescent girls from seven regions in China. Twelve measurements of foot shape were recorded using a video filming system. One-way analysis of variance (ANOVA) compared the changes in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In our country, all the studies carried out in schoolchildren have shown a strong correlation between both parameters [ 14 , 22 ]. This strong correlation has also been observed in other studies carried out in schoolchildren in different ethnic groups [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our country, all the studies carried out in schoolchildren have shown a strong correlation between both parameters [ 14 , 22 ]. This strong correlation has also been observed in other studies carried out in schoolchildren in different ethnic groups [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Several studies reveal ethnic anthropometric differences in the development of foot shape. Asiatic populations such as Japanese children have a wider foot length compared to Caucasoid, Africans and Australoid populations [ 18 , 19 , 20 , 21 ]. After comparing our results with similar studies conducted in Asian schoolchildren, it is observed that this population present shorter foot length at any age and gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of this study sample spans from 3 to 18 years old, encompassing the growth and development process from preschool to the end of puberty, which allowed for a more thorough exploration of growth patterns in height and FL and their associations with puberty development. The most recent studies on FL in China have only covered the ages of 7–12 years old and 13–18 years old separately, which are not age-continuous and do not fully reflect the whole growth and development patterns of children ( 6 , 10 ). Similarly, the latest Spanish study on FL only covers the age range of 3–12 years old, resulting in an incomplete description of growth patterns ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Modes 3, 4, 6–9 were not significant in this study. Mode 3, which corresponds to foot width, surprisingly showed no significant differences between age groups, even though the literature reports a significant increase in foot width at 13–14 years of age in boys [ 42 ]. This may have been due to the wide variance of foot width in our population.…”
Section: Discussionmentioning
confidence: 99%